Pembinaan Eskalasi Mutu Produk Berbasis Cengkeh di Desa Subik Kecamatan Abung Tengah Lampung Utara - Hidayah, Wahyudi; Hidayah, Ridho; Mutiara, Yolanda (Yayasan Daarul Huda Kruengmane, 2024)
Subik village, Abung Tengah subdistrict is home to several plantation commodities, including cloves. This MSME produces dried clove flowers and clove oil and is a partner in this PKM. Apart from improving the quality of partner products and providing laboratory test certificates, the implementation of this PKM broadens partners' understanding of clove cultivation, oil refining, drying clove flowers and product packaging. Implementation, and partner support is the way implementation is carried out. Clove flowers are dried in a closed process in the sun, and clove oil is purified through re-distillation and chelation with citric acid. To increase partner income from sales of these two goods, partners also receive assistance in packaging and marketing the product. Data analysis findings show that partners' knowledge about clove planting according to GAP increased by 40%, about refining clove oil by 70%, about drying clove flowers by 55%, and about product packaging and marketing by 50%. According to SNI 06-2387-2006 standards, Mitra clove oil products have a eugenol concentration of 82%, a density of 1.0275, and a yellow color.